EMOTIONAL STABILITY IN PATIENTS WITH ISCHEMIC HEART DISEASE RESULTING FROM FEAR AND DEPRESSION (Uzbekistan Open Conference, 2025)
Emotional resilience in patients with coronary heart disease is not only a psychological characteristic but also a potential resource capable of significantly impacting the course of the disease, quality of life, and survival. Given the increasing psychological burden and prevalence of chronic diseases, its study is particularly relevant. Emotional resilience has a direct and indirect impact on the course of coronary heart disease, reducing the frequency of exacerbations, improving treatment, decreasing the risk of complications, and increasing overall survival. Emotionally resilient patients have lower levels of chronic stress, anxiety, and fear. Therefore, developing and maintaining emotional resilience should be considered an integral part of the comprehensive treatment of cardiovascular disease.